Perceptions of shellfish aquaculture in British Columbia and implications for well-being in marine social-ecological systems - Linda M. D'Anna; Grant D. Murray (Ecology and Society, 2015)
Shellfish aquaculture is often positioned as an adaptive alternative to traditional resource industries, but the social and cultural effects of expanding production on coastal/marine social-ecological systems are unclear. Reporting on a multimethods study, we present perceptions about shellfish aquaculture collected through interviews, participant-employed photography, and a household survey in British Columbia, Canada. With an approach focused on local preferences for social-ecological conditions and the ways in which those conditions may be enhanced or diminished, we indicate that perceptions of the effects of aquaculture on the environment, economy, and lived experience are composed of both objective and subjective components. Interview responses and survey opinions varied widely and included bimodal responses. Industry interviewees tended to focus on environmental and economic benefits while acknowledging concerns about the environment and lived experience. Nonindustry interviewees typically questioned the environmental effects while underscoring economic benefits and negative effects on experience. Most survey participants felt positively about the effects on the economy, expressed negativity and uncertainty about effects on the environment, and demonstrated the greatest variability in opinions about effects on lived experience. Findings revealed uncertainty and alienation across all dimensions. Our findings, used as an analytical lens, support the usefulness of the concept of well-being in attempts like this one to understand the dynamics of coastal communities by providing a framework for deciphering what is important to individuals and societies experiencing change and considering adaptations.